2016
DOI: 10.1021/acs.macromol.5b02739
|View full text |Cite
|
Sign up to set email alerts
|

Unified Understanding of Ferroelectricity in n-Nylons: Is the Polar Crystalline Structure a Prerequisite?

Abstract: Over the past decades, it has been commonly considered that ferroelectricity is closely related to the polar crystalline structure of odd-numbered nylons, and even-numbered nylons should not exhibit ferroelectricity due to their nonpolar crystalline structures. In this work, we ask a fundamental question: Are odd-numbered nylons with polar crystalline structures prerequisites for ferroelectricity? Here, ferroelectric properties are reported for mesomorphic even-numbered nylons (nylons-12 and -6) quickly quench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 65 publications
5
95
0
Order By: Relevance
“…After subtraction of the AC electronic conduction (the blue horizontal loop), the D‐E loop became typical ferroelectric shaped. This could be ascribed to the increased permittivity for the amorphous nylon‐12 phase when the temperature was above its T g around 45 °C . The maximum D ( D max ) at 200 MV m −1 for QS P6333 was observed at ≈47 mC m −2 with the apparent ε r being ≈35 (Figure A).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…After subtraction of the AC electronic conduction (the blue horizontal loop), the D‐E loop became typical ferroelectric shaped. This could be ascribed to the increased permittivity for the amorphous nylon‐12 phase when the temperature was above its T g around 45 °C . The maximum D ( D max ) at 200 MV m −1 for QS P6333 was observed at ≈47 mC m −2 with the apparent ε r being ≈35 (Figure A).…”
Section: Resultsmentioning
confidence: 95%
“…The broader NH band suggested that hydrogen‐bonding in the nylon‐12 crystals became poorer, confirming the significant structural changes in mesomorphic nylon‐12 crystals for both PEBAX samples after stretching. On the basis of previous reports, we anticipated that these poorly hydrogen‐bonded crystals after stretching should be better to facilitate ferroelectric switching under electric poling.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations